Customers emotional intelligence and satisfaction: The mediation of bankers emotional labour - Ezekiel, Jamo Shedrack; Nanfa, Kusa Danjuma (Annals of Human Resource Management Research, 2023)
Purpose: There is high competition in the Nigerian banking system, with banks challenged by engaging in best practices that will lead to customer satisfaction. This study examines the effect of customers’ emotional intelligence on their satisfaction with selected banks in Nigeria operating in Jos, Plateau. It also assesses customers’ perceptions of banker emotional labor as a mediating factor. Research Methodology: Sample for the study was 341 drawn from customers of Access, UBA, and GT Bank within Jos Metropolis who completed a survey on emotional intelligence, perceived emotional labor, and customer satisfaction. Results: The study found a significant relationship between perceived emotional labor and customer satisfaction and between emotional intelligence and perceived emotional labor. The relationship between emotional intelligence and customer satisfaction is not significant. However, emotional labor was found to be a full mediator in the relationship between emotional intelligence and customer satisfaction. Limitations: There is a limitation in sample size in the study. The actual number of customers from the three banks could not be ascertained. Contribution: The study concluded that bank customer satisfaction is a product of high emotional intelligence when these customers also have a high perception of emotional labor. It is recommended that banks provide brief emotional intelligence training tips for their customers. Novelty: The study has shown that as much as employee emotional intelligence is important to customer satisfaction, customers’ EI is as important. Keywords: Customers, satisfaction, emotional intelligence, emotional labour